A bigger message : conversations with David Hockney - Gayford, Martin, 1952- (London : Thames & Hudson, 2011)
A record of a decade of private conversations with art critic Martin Gayford, David Hockney reveals via reflection, anecdote, passion and humour the fruits of his lifelong meditations on the problems and paradoxes of representing a three-dimensional world on a flat surface.
first published in 2011, updated and expanded paperback edition 2016
boek
Keywords: Hockney, David -- Interviews